2017
DOI: 10.1155/2017/4360357
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Excretion of Kidney Aquaporins as Possible Diagnostic Biomarker of Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is a microangiopathic complication of diabetes mellitus (DM) affecting one-third of diabetic patients. The large variability in the clinical presentation of renal involvement in patients with DM makes kidney biopsy a prerequisite for a correct diagnosis. However, renal biopsy is an invasive procedure associated with risk of major complications. Numerous studies aimed to identify a noninvasive biomarker of DN but, so far, none of these is considered to be sufficiently specific and sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 57 publications
3
46
0
Order By: Relevance
“…Diabetic nephropathy is a microangiopathic complication present in one-third of diabetes mellitus patients [18]. It has been claimed that dysregulation of the water channel membrane protein "aquaporin; AQP" in the kidney plays an important role in the pathogenesis of several kidney diseases including diabetic nephropathy [18][19][20]. Eight AQPs, AQP-1-7 and − 11, are expressed in the kidney to maintain normal urine concentration [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic nephropathy is a microangiopathic complication present in one-third of diabetes mellitus patients [18]. It has been claimed that dysregulation of the water channel membrane protein "aquaporin; AQP" in the kidney plays an important role in the pathogenesis of several kidney diseases including diabetic nephropathy [18][19][20]. Eight AQPs, AQP-1-7 and − 11, are expressed in the kidney to maintain normal urine concentration [20].…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of glomerular AQP-1 is found in all forms of human renal diseases, probably due to compensation for losing cellular integrity [19]. Upregulation of AQP-2 and − 5 is closely related to the progression of diabetic nephropathy in diabetic patients and are good candidates to use for diagnosis [18,24]. Recently, Go and Zhang also reported that an increase in AQP-5 in patients with diabetic nephropathy is independently associated with a reduction in the glomerular filtration rate [25].…”
Section: Discussionmentioning
confidence: 99%
“…The data showed that urinary exosomal bikunin precursor and histone-lysine N-methyltransferase were increased, whereas voltage-dependent anion-selective channel protein 1 was decreased, in DN patients and might lead to the improve diagnostics and monitoring of DN (Zubiri et al, 2014). Later, the increased levels of AQP-2 and AQP-5 were detected in urinary exosomes derived from DN patients, suggesting that these proteins may serve as the non-invasive biomarkers for diagnosis of DN (Rossi et al, 2017). In a subsequent transcriptomics study using miRNAs microarrays, urinary exosomal miR-320c, miR-6068, miR-1234-5p, miR-6133, miR-4270, miR-4739, miR-371b-5p, miR-638, miR-572, miR-1227-5p, miR-6126, miR-1915-5p, miR-4778-5p, and miR-2861 were increased, whereas miR-30d-5p and miR-30e-5p were decreased in type 2 DN patients (Delic et al, 2016).…”
Section: Chronic Kidney Diseasementioning
confidence: 98%
“…Rossi et al . [ 5 ] analyzed the AQP2 and AQP5 (uAQP5 and uAQP2) excreted in urine in 35 patients: 12 diabetic patients with normoalbuminuria and normal renal function, 11 with proteinuria nondiabetic nephropathy, and 12 with histological diagnosis and classification of DKD. Interestingly, the enzyme-linked immunosorbent assay (ELISA) and Western blot analysis independently showed that uAQP5 was significantly increased in DKD patients.…”
Section: U Tility Of U Rinary Ementioning
confidence: 99%
“…[ 3 ] It is also well-known that some diabetic patients could develop renal failure without preexisting albuminuria. [ 5 ] Given increased prevalence and significant socioeconomic burden caused by DKD, the noninvasive and more accurate early diagnostic biomarkers will be needed to improve the quality of patient life and reduce its impact on healthcare.…”
Section: Introductionmentioning
confidence: 99%